High-temperature titanium alloy used for long time in high-temperature, high-pressure and high-rotating-speed extreme environment
A high-temperature titanium alloy with tailored compositions and processes addresses the limitations of existing alloys by providing enhanced creep resistance and mechanical properties, suitable for long-term use in extreme environments of aircraft engines.
Patent Information
- Application Number
- CN202411283672.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-13
AI Technical Summary
Existing titanium alloys used in aircraft engines cannot withstand extreme environments of high temperature (650℃-700℃), high pressure, and high speed for extended periods, necessitating improved materials with enhanced creep resistance and mechanical properties.
A high-temperature titanium alloy with specific compositions and manufacturing processes, including elements like Al, Sn, Zr, Hf, Mo, Nb, Ta, Si, and W, combined with precise forging and heat treatment methods, to achieve a fine lamellar structure and balanced mechanical properties.
The alloy exhibits excellent strength, creep resistance, and super-rotation rupture performance at 650℃-700℃, suitable for long-term use in extreme environments, meeting the stringent requirements of new-generation aircraft engines.
Smart Images

Figure CN119242984A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal materials, and in particular to a high-temperature titanium alloy used for a long time in extreme environments of high temperature, high pressure and high rotation speed. Background Art
[0002] Advanced aircraft engines are constantly developing towards high turbine pre-temperature, high thrust-to-weight ratio, and high compression ratio, which are mainly achieved by increasing component working stress, reducing component weight, and increasing stiffness. Compared with other commonly used materials, titanium alloys have significant advantages in specific strength, specific stiffness, and specific low-cycle fatigue strength, and have a significant weight reduction effect. They can significantly improve the engine thrust-to-weight ratio and service performance, and are the only choice for the preparation of aircraft engine components.
[0003] Key parts of aircraft engine blisks, blades, turbine disks, etc. work under high temperature, high pressure, high load and multi-load environment conditions for a long time. At present, the highest long-term service temperature of titanium alloy parts is 500℃~600℃, and the short-term service temperature is about 650℃~700℃, which is generally between tens of minutes and several hours. This is the extreme high temperature working state of existing aircraft engine titanium alloy parts.
[0004] The new generation of engines has higher operating temperatures, more complex and severe stresses, and more stringent performance requirements for materials. Therefore, it is urgent to design a high-temperature titanium alloy that can be used for a long time in extreme environments of high temperature, high pressure and high speed. Summary of the invention
[0005] In view of the above analysis, an embodiment of the present invention aims to provide a high-temperature titanium alloy for long-term use in extreme environments of high temperature, high pressure and high speed, so as to solve the problem in the prior art that titanium alloy parts of aviation engines cannot serve for a long time in extreme working environments of high temperature (650℃-700℃), high pressure and high speed.
[0006] In the first aspect, an embodiment of the present invention provides a high-temperature titanium alloy, the chemical composition and weight percentage of the high-temperature titanium alloy are Al: 6.0%-8.0%, Sn: 2.5%-4.5%, Zr: 2.5%-7.0%, Hf: 0.5%-1.5%, Mo: 0.05%-0.85%, Nb: 0.20%-0.80%, Ta: 1.0%-3.0%, Si: 0.40%-0.90%, W: 0.4%-1.0%, C: 0.05%-0.07%, and Ti as a remainder.
[0007] Furthermore, according to the high temperature titanium alloy of claim 1, in the chemical composition and weight percentage of the high temperature titanium alloy, when Ta≤2.0%, Si≥0.6%.
[0008] Furthermore, the chemical composition and weight percentage of the high-temperature titanium alloy are Al: 6.0%-8.0%, Sn: 2.5%-4.5%, Zr: 2.5%-3.5%, Hf: 0.5%-1.0%, Mo: 0.05%-0.85%, Nb: 0.20%-0.80%, Ta: 1.0%-3.0%, Si: 0.5%-0.9%, W: 0.4%-1.0%, C: 0.05%-0.07%, and Ti as a balance.
[0009] Furthermore, the chemical composition and weight percentage of the high-temperature titanium alloy are: Al: 6.0%, Sn: 3.8%, Zr: 2.5%, Hf: 1%, Mo: 0.30%, Nb: 0.40%, Ta: 2.3%, Si: 0.60%, W: 0.80%, C: 0.05%-0.07%, Ti: balance.
[0010] Furthermore, the chemical composition and weight percentage of the high temperature titanium alloy are: Al: 6.0%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 1.0%, Si: 0.90%, W: 0.80%, C: 0.05%-0.07%, Ti: balance.
[0011] Furthermore, the R m ≥1000MPa, R p0.2 ≥900MPa, A5≥6%; R at 650℃ m ≥610MPa, R p0.2 ≥500MPa; creep residual strain under the test conditions of temperature 650℃, creep stress 120MPa and time 100h ≤0.18%; R at 700℃ m ≥560MPa, R p0.2 ≥450MPa; creep residual strain ≤0.18% under the test conditions of temperature 700℃, creep stress 70MPa and test time 100h.
[0012] In a second aspect, an embodiment of the present invention provides a method for preparing the above-mentioned high temperature titanium alloy, the method comprising:
[0013] (1) according to the chemical composition and weight percentage of the high-temperature titanium alloy, weighing the metal and / or the master alloy, smelting, and obtaining a titanium alloy ingot;
[0014] (2) forging and deforming the titanium alloy ingot to obtain a forging blank;
[0015] (3) The forging blank is subjected to solution heat treatment and aging heat treatment in sequence to obtain the high-temperature titanium alloy.
[0016] Furthermore, in step (2), the forging deformation specifically includes a first stage upsetting, a first heat treatment and a first stage upsetting, wherein the first stage upsetting includes three-stage upsetting, specifically: the titanium alloy ingot is subjected to one-stage upsetting deformation at temperatures of 1150°C to 1400°C, 1100°C to 1300°C, and 1000°C to 1100°C, respectively, and the deformation amount is controlled at 40%-50%.
[0017] Furthermore, in step (3), the temperature of the solution heat treatment is T β -25℃~T β -10℃, time is 1-3h;
[0018] Furthermore, the temperature of the aging heat treatment is 700°C-800°C, and the time is 4-7h.
[0019] In a third aspect, an embodiment of the present invention provides an application of the above-mentioned high-temperature titanium alloy in the manufacture of aircraft engine parts, wherein the aircraft engine parts are blisks, blades, turbine disks, etc.
[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0021] 1. The element Hf in the high-temperature titanium alloy of the present invention improves the oxidation resistance and creep resistance of the alloy at high temperatures; the element Zr has a strong high-temperature strengthening effect, and the composite strengthening effect formed with the Sn element is higher than that of a single element, and can refine the silicide in the alloy and promote the dispersion distribution of the silicide, hindering the growth of the original β grains, thereby obtaining a fine lamellar structure, achieving the effect of improving the creep performance without reducing the plasticity of the alloy;
[0022] Increasing the Ta content can improve the creep properties of the alloy and also improve the material's oxidation resistance; the solid solution strengthening and precipitation strengthening effects of Si can significantly improve the high temperature creep properties of the alloy;
[0023] The element W in the alloy can form a composite phase with titanium, such as β1(Ti,W) titanium-rich phase and β2(Ti,W) tungsten-rich phase, which improves the density and mechanical properties of the alloy.
[0024] By adjusting the composition and content ratio of alloy elements, the titanium alloy has excellent strength, creep resistance and super-rotation rupture performance at high temperatures of 650℃-700℃, making it suitable for long-term use in extreme environments of high temperature, high pressure and high speed, and meeting the requirements of extreme high temperature working conditions of new generation aircraft engine titanium alloy parts (integral blades).
[0025] 2. The content of Si in the existing titanium alloy is relatively low (less than 0.6%), so as to avoid the formation of too many sub-grained α phases in the alloy due to too high Si content, resulting in insufficient toughness of the titanium alloy. Different from the existing titanium alloy, the present invention ensures the improvement of the creep performance of the alloy by increasing the Si content when the Ta content cannot be too high. However, too high Si content will reduce the plasticity and creep performance of the alloy due to the uneven precipitation of silicide precipitation phase. Therefore, the element Zr is added to the alloy to promote the dispersed distribution of the silicide precipitation phase, so that when the Si content is high (0.9%), there will be no defects such as segregation, and the alloy composition is uniform (such as Figure 2 shown).
[0026] 3. The element W in the high-temperature titanium alloy of the present invention can refine the grain structure of the titanium alloy, improve the high-temperature strength and creep resistance of the titanium alloy, which is crucial for titanium alloy parts that work for a long time under high temperature conditions; however, excessive addition of tungsten elements may also cause segregation and embrittlement of the structure, resulting in a decrease in the creep resistance of the alloy. The content of W in the high-temperature alloy of the present invention is controlled at 0.4%-1.0%.
[0027] 4. The present invention adjusts the composition and content of the high-temperature titanium alloy so that it has higher tensile strength (≥610MPa) and yield strength (≥500MPa) at 650°C to adapt to the high-temperature working environment of 650°C; and under the conditions of high temperature of 650°C and high creep stress of 120MPa, it has better creep resistance, and the creep residual strain under the test time of 100h is ≤0.18%; at 700°C, it still has higher tensile strength (≥560MPa) and yield strength (≥450MPa) to adapt to the extreme high-temperature working environment; and under the conditions of high temperature of 700°C and high creep stress of 70MPa, it still has better creep resistance, and the creep residual strain under the test time of 100h is ≤0.18%; the high-temperature titanium alloy of the present invention is suitable for preparing parts in extreme high-temperature working conditions, such as aircraft engine parts that work for a long time in extreme environments of high temperature, high pressure and high speed, to promote the development and progress of aerospace.
[0028] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0030] Figure 1 This is a microstructure diagram of the high temperature titanium alloy forging 1 prepared in Example 1;
[0031] Figure 2 This is a microstructure diagram of the high temperature titanium alloy forging 2 prepared in Example 2;
[0032] Figure 3 This is a microstructure diagram of the high temperature titanium alloy forging 3 obtained in Example 3;
[0033] Figure 4 This is a microstructure diagram of the high temperature titanium alloy forging 4 prepared in Example 4;
[0034] Figure 5 This is a microstructure diagram of the high temperature titanium alloy forging 5 obtained in Example 5;
[0035] Figure 6 The super-rotation test curve of the integral blade made of high-temperature titanium alloy forging 1 under the condition of 650℃ / 115%;
[0036] Figure 7 The super-rotation test curve of the integral blade made of high-temperature titanium alloy forging 1 under the condition of 650℃ / 122%;
[0037] Figure 8 This is the super-rotation test curve of the integral blade made of high-temperature titanium alloy forging 1 under 650℃ / 150% conditions. DETAILED DESCRIPTION
[0038] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0039] Key parts of aircraft engines, such as blisks and blades, work under high temperature, high pressure, high load and multi-load conditions for a long time. At present, the highest long-term service temperature of titanium alloy parts is 500℃~600℃, and the short-term service temperature is about 650℃~700℃, which is generally between tens of minutes and hours, which is the extreme high temperature working state of existing aircraft engine titanium alloy parts. The new generation of engines has higher operating temperatures, more complex and severe stresses, and more stringent performance requirements for materials.
[0040] Therefore, the present invention provides a high-temperature titanium alloy, the chemical composition and weight percentage of the high-temperature titanium alloy are Al: 6.0%-8.0%, Sn: 2.5%-4.5%, Zr: 2.5%-7.0%, Hf: 0.5%-1.5%, Mo: 0.05%-0.85%, Nb: 0.20%-0.80%, Ta: 1.0%-3.0%, Si: 0.40%-0.90%, W: 0.4%-1.0%, C: 0.05%-0.07%, and Ti balance.
[0041] The following is a detailed description of the effects and dosage of the components in the present invention:
[0042] Al: It has a significant solid solution strengthening effect, which can improve the mechanical properties of the alloy, especially the ability to withstand greater stress and load in high temperature environments; improve oxidation resistance; increasing the phase transition temperature helps maintain the stability of the structure in high temperature environments, thereby increasing its service life; improving thermal strength, so that the alloy maintains strength in high temperature environments. Higher than 6.0% is to ensure the room temperature, high temperature strength and thermal strength of the alloy, but when the Al content is higher than 8.0%, too much α2 phase will precipitate during use, reducing the thermal stability of the alloy, and will reduce the alloy's plasticity and toughness, and the process performance will deteriorate.
[0043] Sn: Improves the strength of the alloy through solid solution strengthening; Improves heat resistance, that is, maintains high strength at high temperatures; Controlling the content above 2.5% is to achieve higher room temperature strength and high temperature strength. Too high Sn content (greater than 4.5%) may form an ordered phase (such as Ti3Sn), reducing the plasticity and thermal stability of the alloy.
[0044] Mo: Mo improves the strength of the alloy through solid solution strengthening. It has an important influence on the thermal stability and creep properties of the alloy. The addition of Mo can improve the high temperature durability and creep properties of the alloy, so that it can still maintain high strength and stability at high temperatures. It can also improve the processing performance (reduce the tendency of forging cracking), and synergize with other alloying elements (such as Al, Sn, Zr, etc.), such as producing a more complex and stable β-phase structure with a body-centered cubic structure (bcc) at higher temperatures, thereby improving the strength and heat resistance of the alloy. If the Mo content is too high (above 0.85%), it will not only inhibit the precipitation of silicides and reduce creep properties, but also reduce plasticity, increase the deformation resistance and thermal cracking tendency of the alloy, and make processing more difficult. If Mo and W are not added to the alloy, the tensile strength will drop sharply when the use temperature reaches above 600°C.
[0045] Nb: It improves the strength of the alloy through solid solution strengthening, improves the alloy's thermal strength and creep properties, and works in synergy with other alloying elements (such as Al, Sn, Zr, etc.) to produce a more complex and stable phase structure, including solid solution, intermetallic compounds (titanium-aluminum-niobium W phase) and complex precipitation phases, thereby improving the strength and heat resistance of the alloy. If the Nb content is too high (above 0.8%), on the one hand, it is easy to cause component segregation, and it will also reduce plasticity, increase the alloy's deformation resistance and thermal cracking tendency, making processing more difficult.
[0046] C: Too high a content will cause carbides to precipitate, reducing the plasticity and toughness of the alloy and causing poor processing performance. It will also reduce high-temperature creep performance (carbides will become the starting point and path for creep crack expansion). Adding a small amount of C is to expand the process window.
[0047] Zr: Zr has a strong high-temperature strengthening effect. The composite strengthening effect formed with Sn is higher than that of a single element. It can also refine the silicides in the alloy and promote the dispersion distribution of the silicides, hindering the growth of the original β grains, thereby obtaining a fine lamellar structure with an average lamellar spacing of 0.25-0.30 μm, thereby achieving the effect of improving the creep performance without reducing the plasticity of the alloy. However, too much Zr will reduce the solubility of Si, thereby affecting the precipitation behavior and performance of the alloy. Therefore, the present invention controls the content of Zr in the alloy to 2.5%-7.0%, and more preferably to 2.5%-3.5%.
[0048] Hf: Hf improves the oxidation resistance and creep resistance of the alloy at high temperatures. The Hf element works synergistically with other alloying elements to produce a more complex and stable phase structure, thereby improving the heat resistance of the alloy. However, when the content is too high, it is easy to segregate, which will reduce the high-temperature strength, significantly reduce the room temperature plasticity and high-temperature plasticity, and is expensive. Therefore, the content should not be too high, and is 0.5%-1.5%, preferably 0.5%-1.0%.
[0049] Ta: Ta will form a composite solid solution strengthening with W to improve the high-temperature tensile strength. Increasing the Ta content can improve the creep performance of the alloy and the oxidation resistance of the material. However, too high a Ta content will have no significant effect on improving the creep performance and oxidation resistance of the material, and will also reduce the plasticity of the alloy, increase the cost and difficulty of the processing technology. The Ta content of the present invention is 1.0%-3.0%.
[0050] Si: When the Ta content is not too high, the creep performance of the alloy can be improved by increasing the Si content. The solid solution strengthening and precipitation strengthening effects of the element Si can significantly improve the high-temperature creep performance of the alloy. For existing titanium alloys, an Si content greater than 0.6% will reduce the plasticity and creep performance of the alloy due to the uneven precipitation of the silicide precipitate phase. During the research on titanium alloys, the inventors of the present application have conducted many experiments and found that when the Si content is increased to improve the creep resistance of the alloy, the addition of the element Zr can prevent the uneven precipitation of the silicide precipitate phase, promote the dispersed distribution of the silicide precipitate phase, strengthen the grain boundary, and improve the strength and other properties of the alloy. After the synergistic effect of high-content Si and Zr, the dispersed silicide can hinder dislocation and grain boundary sliding and improve creep performance. The Si content of the present invention is 0.4%-0.9%, which breaks through the upper limit of the silicon content in existing titanium alloys.
[0051] W: The element W in the alloy can form a composite phase with titanium, such as β1 (Ti, W) titanium-rich phase and β2 (Ti, W) tungsten-rich phase, to improve the high-temperature strength and creep resistance of the titanium alloy, which is crucial for titanium alloy parts that work for a long time under high temperature conditions; however, excessive addition of tungsten may also lead to segregation and embrittlement of the structure, resulting in a decrease in the creep resistance of the alloy. The W content in the high-temperature alloy of the present invention is controlled at 0.4%-1.0%.
[0052] Specifically, the microstructure of the high temperature titanium alloy of the present invention is a dual-state structure, including an equiaxed α phase and a β transformation structure, and the β transformation structure contains a lamellar β phase and a lamellar α phase, the latter of which is also called a secondary α phase or a secondary α phase; wherein, the equiaxed α phase is beneficial to the hardness and strength of the titanium alloy, and helps to improve the thermal stability of the alloy, and the β transformation structure is beneficial to the toughness and plastic deformation ability of the titanium alloy, so the dual-state structure can balance the strength and plasticity of the alloy to a certain extent. By adjusting the composition and ratio of the titanium alloy, the type and parameters of the dual-state structure can be adjusted within a certain range to achieve the best matching of the mechanical properties of the alloy, and the titanium alloy parts can be improved under the condition of ensuring the instantaneous mechanical properties (tensile strength, yield strength) of the titanium alloy under high temperature conditions. The long-term service ability of the titanium alloy parts under extreme conditions of high temperature, high pressure and high speed. In the microstructure of the high temperature titanium alloy of the present invention, the content of the equiaxed α phase is 6%-15%. According to some specific embodiments of the present invention, in the microstructure of the high temperature titanium alloy, the content of the equiaxed α phase is 9.74%, 6.4%, 13.80%, 9.34% or 6.14%, respectively.
[0053] In order to ensure the improvement of the creep performance of the alloy, the present invention ensures the improvement of the creep performance of the alloy by increasing the Si content when the Ta content is low. Specifically, in the chemical composition and weight percentage of the high-temperature titanium alloy, when Ta≤2.0%, Si≥0.6%; when Ta>2.0%, Si 0.40%-0.90%.
[0054] In order to further improve the comprehensive properties of the above-mentioned high-temperature titanium alloy, the components of the above-mentioned high-temperature titanium alloy may be, by mass percentage, Al: 6.0%-8.0%, Sn: 2.5%-4.5%, Zr: 2.5%-3.5%, Hf: 0.5%-1.0%, Mo: 0.05%-0.85%, Nb: 0.20%-0.80%, Ta: 1.0%-3.0%, Si: 0.5%-0.9%, W: 0.4%-1.0%, C: 0.05%-0.07%, and the remainder is titanium and inevitable trace impurities.
[0055] According to a preferred embodiment of the present invention, the chemical composition and weight percentage of the high-temperature titanium alloy are: Al: 6.0%, Sn: 3.8%, Zr: 2.5%, Hf: 1.0%, Mo: 0.3%, Nb: 0.4%, Ta: 2.3%, Si: 0.6%, W: 0.8%, C: 0.05%-0.07%, Ti: balance.
[0056] According to a preferred embodiment of the present invention, the chemical composition and weight percentage of the high-temperature titanium alloy are: Al: 6.0%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 1.0%, Si: 0.90%, W: 0.80%, C: 0.05%-0.07%, Ti: balance.
[0057] According to a preferred embodiment of the present invention, the chemical composition and weight percentage of the high-temperature titanium alloy are: Al: 6.0%, Sn: 4.0%, Zr: 3.0%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 2.0%, Si: 0.70%, W: 0.80%, C: 0.05%-0.07%, Ti: balance.
[0058] According to a preferred embodiment of the present invention, the chemical composition and weight percentage of the high-temperature titanium alloy are: Al: 6.0%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 2.5%, Si: 0.50%, W: 0.80%, C: 0.05%-0.07%, Ti: balance.
[0059] According to a preferred embodiment of the present invention, the chemical composition and weight percentage of the high-temperature titanium alloy are: Al: 5.9%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 2.0%, Si: 0.70%, W: 0.8%, C: 0.05%-0.07%, Ti: balance.
[0060] By adjusting the alloy element composition and content ratio, it not only has excellent mechanical properties at room temperature, but also has excellent mechanical properties. m ≥1000MPa, R p0.2 ≥900MPa, A5≥6%; and it has excellent strength and creep resistance at high temperatures of 650-700℃. Specifically, the short-term mechanical properties in the 600℃-700℃ environment meet the design requirements: at 600℃, R m ≥700MPa, R p0.2 ≥600MPa; at 650℃, R m ≥610MPa, R p0.2 ≥500MPa; at 700℃, R m ≥560MPa, R p0.2 ≥450MPa; The creep resistance in 600℃-700℃ environment meets the design requirements, the creep residual strain at 700℃ / 70MPa / 100h is ≤0.18%, the creep residual strain at 650℃ / 120MPa / 100h is ≤0.18%, and the creep residual strain at 600℃ / 160MPa / 100h is ≤0.12%.
[0061] The invention characterizes the mechanical properties of high temperature titanium alloy forging products according to the testing standards GB / T 228.1, GB / T 228.2 and GB / T 2039, and obtains microstructure photos of the forging products through a metallographic microscope.
[0062] The present invention also provides a method for preparing the above-mentioned high-temperature titanium alloy, comprising smelting, forging and heat treatment, specifically comprising:
[0063] (1) weighing metal and / or intermediate alloy raw materials according to the chemical composition and weight percentage of the high-temperature titanium alloy, smelting, and obtaining a titanium alloy ingot;
[0064] (2) forging and deforming the titanium alloy ingot to obtain a forging blank;
[0065] (3) Heat treating the forging blank to obtain the high-temperature titanium alloy.
[0066] Specifically, in step (1), the raw material is pure Al, sponge zirconium, sponge titanium, Ti-Sn, Ti-Hf, Ti-Mo or Al-Mo, Ti-Ta or Al-Ta, Ti-Nb or Al-Nb, Al-Si, Al-W and other intermediate alloys.
[0067] Specifically, in step (1), the smelting is vacuum consumable electrode smelting. The specific steps are: first, the raw materials other than sponge titanium are uniformly mixed by a mixing machine to obtain a mixed raw material; second, the sponge titanium is evenly divided into three parts, and the mixed raw material is divided into two parts, and the sponge titanium, mixed raw material, sponge titanium, mixed raw material, and sponge titanium are evenly placed in a mold in the order of sponge titanium, mixed raw material, sponge titanium, mixed raw material, and sponge titanium to form an electrode, and the electrodes are welded to obtain a consumable electrode; third, a titanium alloy ingot with uniform composition is obtained by three vacuum consumable smelting methods, and shrinkage cavities and surface oxide scale are removed.
[0068] Specifically, in step (2), the forging deformation specifically includes a first stage upsetting, a primary heat treatment and a second stage upsetting.
[0069] According to a preferred embodiment of the present invention, the first stage upsetting includes three-stage upsetting, and the specific process includes: the titanium alloy ingot is subjected to 1-2 upsetting deformations at 1150℃~1400℃, 1100℃~1300℃, and 1000℃~1100℃ in sequence, and the deformation is controlled at 40%-50%; the one-stage upsetting can not only break the rough β grains, but also play a uniform annealing role, further promote the homogenization of the composition, and in addition, the temperature is gradually reduced, which can inhibit the growth of grains when the β zone is heated. The temperature of the first upsetting should be about 200-250℃ above the phase transition point, because the original ingot has coarse grains and large deformation resistance. After the first stage upsetting, the grains are broken; the second upsetting has a lower deformation resistance than the first upsetting, so the deformation temperature is lowered, but it still needs to be above the phase transition point. This step is to further refine the grains; similarly, the temperature of the third upsetting is lower than that of the second upsetting.
[0070] According to a preferred embodiment of the present invention, the temperature of the primary heat treatment is T β +10℃~T β +40℃ to reduce the structural inhomogeneity at the edge and core of the alloy and promote structural homogenization; the heating time is related to the specifications of the prepared bars or forgings, for example, for a bar with a diameter of 210mm, the holding time is about 240min-300min.
[0071] Specifically, in order to improve the uniformity of the temperature of the entire forging and avoid thermal stress, deformation, cracking and other problems caused by directly heating to the heat treatment temperature, the forging needs to be preheated before heat treatment, and the preheating temperature is 950℃-980℃.
[0072] According to a preferred embodiment of the present invention, the second stage upsetting is performed at T β -50℃~T βThe upsetting deformation is carried out for 3 to 10 times at a temperature of -10°C. The deformation amount of the second stage upsetting deformation is 40%-50%. This process obtains fine-grained, equiaxed and uniform structure through multiple upsetting deformations, further promoting the homogenization of the alloy structure.
[0073] After the first stage of upsetting and homogenization heat treatment, the grains have been initially refined, so the deformation temperature can be reduced to below the phase transition point. The deformation in this stage is to further refine the grain size. If the temperature is too high, the grains will grow again. The greater the deformation, the better the grain refinement. The deformation is related to the deformation resistance of the alloy itself. Within the allowable range of deformation resistance, the greater the better. If it exceeds 50%, there may be cracks.
[0074] According to a preferred embodiment of the present invention, after the second stage upsetting, the process further comprises: according to the design requirements of the target forging product, at T β -50℃~T β Forming is performed at a temperature of -10°C to obtain a target forging blank;
[0075] Preferably, the target forging is an integral blisk.
[0076] Forging deformation obtains uniform processed structure. Solution aging heat treatment is a comprehensive strengthening process, the main purpose of which is to improve the strength and creep resistance of titanium alloys, while maintaining or improving their plasticity and toughness, in order to obtain excellent comprehensive mechanical properties.
[0077] Specifically, in step (3), the heat treatment includes solution heat treatment and aging heat treatment.
[0078] The purpose of solution heat treatment is to dissolve the phase and form a uniform solid solution. Reduce the stress concentration at the grain boundary and phase boundary to prepare for the subsequent aging treatment. Furthermore, the use of optimized water cooling can obtain a refined grain structure and improve the strength of the alloy. Ensure that the phase can be dissolved and precipitated within the solution heat treatment time.
[0079] The purpose of aging heat treatment is to re-precipitate the strengthening phase evenly, form a fine dispersed strengthening phase, improve the alloy strength and improve the stability of the structure, reduce the changes in the structure (such as phase change, grain growth, etc.) during high temperature or long-term use, and thus improve the creep resistance and thermal stability of the material. The precipitation of the aging phase is guaranteed within the aging time. If the time is too long, the grains will coarsen; element diffusion and phase change will occur, and the stability of the structure will also deteriorate.
[0080] According to a preferred embodiment of the present invention, the temperature of the solution heat treatment is T β -25℃~T β -10℃, time 1-3h, water cooling or air cooling, preferably water cooling.
[0081] According to a preferred embodiment of the present invention, the aging heat treatment is performed at a temperature of 700-800° C. for 4-7 hours with air cooling.
[0082] Solution-aging heat treatment combines solution treatment with aging treatment. By dissolving first and then precipitating, the elements in the alloy are distributed more evenly and the precipitated phase is finer and dispersed, thereby significantly improving the hardness, strength, wear resistance and corrosion resistance of the alloy, while ensuring the alloy's high-temperature creep resistance, good toughness and plasticity.
[0083] In a third aspect, an embodiment of the present invention provides an application of the above-mentioned high-temperature titanium alloy in aircraft engine parts, wherein the aircraft engine parts are blisks, blades, and turbine disks.
[0084] According to a preferred embodiment of the present invention, the high-temperature titanium alloy of the present invention is applied to the integral blade disk of an aero-engine. The over-rotation rupture performance of the high-temperature titanium alloy integral blade disk is tested under a high temperature, high pressure and high speed environment. It is found that after the over-rotation test at 650°C and 115% speed, the size did not change significantly and no visible cracks were found; after the over-rotation test at 122% speed, the size did not change significantly and no visible cracks were found; after the over-rotation test at 150% speed, there was no significant change in the size and no visible cracks were found; after the over-rotation test at 150%, the size did not change significantly and the test piece was broken.
[0085] The present invention adjusts the composition and content of high-temperature titanium alloy and cooperates with reasonable preparation process and parameters to make high-temperature titanium alloy parts have excellent strength, creep resistance and super-rotation rupture performance at high temperatures of 650℃-700℃, and adapt to extreme high-temperature working environments; it provides design and material selection for parts of advanced aircraft engines and other weapons and equipment in extreme service environments such as high temperature, high pressure, and high speed, and improves the service life of aircraft engines and other equipment in harsh environments.
[0086] The technical solution of the present invention is further demonstrated by specific examples and comparative examples below, wherein the preparation method of the high temperature titanium alloy ingot in the examples and comparative examples is the same, specifically comprising:
[0087] (1) weighing raw materials according to the mass ratio of high-temperature titanium alloy, including pure Al, sponge zirconium, intermediate alloys Ti-Sn, Ti-Hf, Ti-Mo, Al-Nb, Ti-Ta, Al-Si and Al-W, carbon powder and sponge titanium, and mixing the raw materials except sponge titanium with a mixer to obtain a mixed material;
[0088] (2) The weighed titanium sponge is evenly divided into three parts and the mixed material is evenly divided into two parts, and the sponge titanium, the mixed material, the sponge titanium, the mixed material, and the sponge titanium are evenly placed in a mold in the order of sponge titanium, mixed material, sponge titanium, mixed material, and sponge titanium to form electrodes, and the electrodes are welded together to obtain consumable electrodes; a high-temperature titanium alloy ingot with uniform composition is obtained by three vacuum consumable melting methods, and shrinkage cavities and surface oxide scales are removed.
[0089] The following examples and comparative examples process and heat treat their respective specific high-temperature titanium alloy ingots, test the mechanical properties of the forged products according to standards GB / T 228.1, GB / T 228.2 and GB / T 2039, and obtain microstructure photographs of the forged products through a metallographic microscope.
[0090] Example 1
[0091] The chemical composition and weight percentage of the high temperature titanium alloy ingot 1 are: Al: 6.0%, Sn: 3.8%, Zr: 2.5%, Hf: 1.0%, Mo: 0.3%, Nb: 0.4%, Ta: 2.3%, Si: 0.6%, W: 0.8%, C: 0.055%, Ti: balance.
[0092] The steps of processing and heat treating the high temperature titanium alloy ingot 1 include:
[0093] (1) a high temperature titanium alloy ingot 1 is subjected to upsetting deformation at temperatures of 1180° C., 1120° C. and 1030° C., respectively, with a total deformation of 45%;
[0094] After measurement, the T of the titanium alloy after the first stage of upsetting β The first heat treatment is 1045℃, and the temperature is kept at 950℃ for 180min, then the temperature is raised to 1070℃ with the furnace and kept for 120min, and then taken out of the furnace and air-cooled;
[0095] The second stage of upsetting: 8 times of upsetting deformation at 1030℃, with a deformation of 45%;
[0096] (2) The forging obtained in step (1) is subjected to solution aging heat treatment: at a temperature of 1025° C., kept for 2 h, and air-cooled; at a temperature of 700° C., kept for 5 h, and air-cooled, to obtain a high-temperature titanium alloy forging 1.
[0097] The microstructure photo of high temperature titanium alloy forging 1 is shown in Figure 1 As shown, from Figure 1 It can be seen that the microstructure phase distribution is relatively uniform; through testing, the equiaxed α phase content is 9.74%, the average size is 4.50μm, and the average interlamellar spacing is 0.24μm.
[0098] The mechanical properties of high temperature titanium alloy forging 1 are shown in Table 1:
[0099] Table 1
[0100]
[0101] Example 2
[0102] The chemical composition and weight percentage of the high temperature titanium alloy ingot 2 are: Al: 6.0%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 1.0%, Si: 0.90%, W: 0.80%, C: 0.055%, Ti: balance.
[0103] The steps of processing and heat treating the high temperature titanium alloy ingot 2 include:
[0104] (1) The high temperature titanium alloy ingot 2 is subjected to two times of upsetting deformation at temperatures of 1150° C., 1100° C. and 1000° C., respectively, with a total deformation of 40%;
[0105] After measurement, the T of the titanium alloy after the first stage of upsetting β The first heat treatment is 1045℃: keep the temperature at 980℃ for 120min, then heat up to 1085℃ and keep the temperature for 120min, then take out of the furnace and air cool;
[0106] The second stage of upsetting: 3 times of upsetting deformation at 1035℃, with a deformation of 50%;
[0107] (2) The forging obtained in step (1) is subjected to solution aging heat treatment: at a temperature of 1020°C, keeping warm for 2 hours, and air cooling; at a temperature of 800°C, keeping warm for 5 hours, and air cooling, to obtain a high-temperature titanium alloy forging 2.
[0108] The microstructure photo of high temperature titanium alloy forging 2 is shown in Figure 2 As shown, from Figure 2 It can be seen that the microstructure phase distribution is relatively uniform; through testing, the equiaxed α phase content is 6.4%, the average size is 3.40μm, and the average interlamellar spacing is 0.25μm.
[0109] The mechanical properties of high temperature titanium alloy forging 2 are shown in Table 2:
[0110] Table 2
[0111]
[0112] Example 3
[0113] The chemical composition and weight percentage of the high temperature titanium alloy ingot 3 are: Al: 6.0%, Sn: 4.0%, Zr: 3.0%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 2.0%, Si: 0.70%, W: 0.80%, C: 0.055%, Ti: balance.
[0114] The steps of processing and heat treating the high temperature titanium alloy ingot 3 include:
[0115] (1) The high temperature titanium alloy ingot 3 is subjected to upsetting deformation at 1400° C., 1300° C. and 1100° C., respectively, with a total deformation of 50%;
[0116] After measurement, the T of the titanium alloy after the first stage of upsetting β 1052℃, primary heat treatment: keep at 950℃ for 120min, then heat up to 1062℃ with the furnace and keep for 180min, then take out of the furnace and air cool;
[0117] The second stage of upsetting: 10 times of upsetting deformation at 1005℃, with a deformation of 45%;
[0118] (2) The forging obtained in step (1) is subjected to solution aging heat treatment: at a temperature of 1040°C, keeping warm for 2 hours, and air cooling; at a temperature of 750°C, keeping warm for 5 hours, and air cooling, to obtain a high-temperature titanium alloy forging 3.
[0119] The microstructure photo of high temperature titanium alloy forging 3 is shown in Figure 3 As shown, from Figure 3 It can be seen that the microstructure phase distribution is relatively uniform; through testing, the equiaxed α phase content is 11.44%, the average size is 4.23μm, and the average interlamellar spacing is 0.28μm.
[0120] The mechanical properties of high temperature titanium alloy forging 3 are shown in Table 3:
[0121] Table 3
[0122]
[0123] Example 4
[0124] The chemical composition and weight percentage of the high temperature titanium alloy ingot 4 are: Al: 6.0%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 2.5%, Si: 0.50%, W: 0.80%, C: 0.055%, Ti: balance.
[0125] The steps of processing and heat treating the high temperature titanium alloy ingot 4 include:
[0126] (1) The high temperature titanium alloy ingot 3 is subjected to upsetting deformation at 1180° C., 1120° C. and 1030° C., respectively, with a total deformation of 40%;
[0127] After measurement, the T of the titanium alloy after the first stage of upsetting β The temperature is 1040℃, and the primary heat treatment is: keep the temperature at 950℃ for 180min, then heat up to 1060℃ with the furnace and keep the temperature for 120min, then take out of the furnace and air cool;
[0128] The second stage of upsetting: 8 times of upsetting deformation at 1030℃, with a deformation of 45%;
[0129] (2) The forging obtained in step (1) is subjected to solution aging heat treatment: at a temperature of 1020° C., kept for 2 h, and air-cooled; at a temperature of 700° C., kept for 5 h, and air-cooled, to obtain a high-temperature titanium alloy forging 4.
[0130] The microstructure photo of high temperature titanium alloy forging 4 is shown in Figure 4 As shown, from Figure 4 It can be seen that the microstructure phase distribution is relatively uniform; through testing, the equiaxed α phase content is 9.34%, the average size is 4.82μm, and the average interlamellar spacing is 0.29μm. Mechanical properties are shown in Table 4:
[0131] Table 4
[0132]
[0133] Example 5
[0134] The chemical composition and weight percentage of the high temperature titanium alloy ingot 5 are: Al: 5.9%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 2%, Si: 0.70%, W: 0.80%, C: 0.055%, Ti: balance.
[0135] The steps of processing and heat treating the high temperature titanium alloy ingot 5 include:
[0136] (1) The high temperature titanium alloy ingot 5 is subjected to upsetting deformation at 1180° C., 1120° C. and 1030° C., respectively, with a total deformation of 45%;
[0137] After measurement, the T of the titanium alloy after the first stage of upsetting β The temperature is 1040℃, and the primary heat treatment is: keep the temperature at 950℃ for 180min, then heat up to 1065℃ and keep the temperature for 120min, then take out of the furnace and air cool;
[0138] The second stage of upsetting: 8 times of upsetting deformation at 1030℃, with a deformation of 45%;
[0139] (2) The forging obtained in step (1) is subjected to solution aging heat treatment: at a temperature of 1020° C., kept for 2 h, and air-cooled; at a temperature of 700° C., kept for 5 h, and air-cooled, to obtain a high-temperature titanium alloy forging 5.
[0140] The microstructure photo of high temperature titanium alloy forging 5 is as follows Figure 5 As shown, from Figure 5 It can be seen that the microstructure phase distribution is relatively uniform; through testing, the equiaxed α phase content is 6.14%, the average size is 3.39μm, and the average interlamellar spacing is 0.23μm. Mechanical properties are shown in Table 5:
[0141] Table 5
[0142]
[0143] Comparative Example 1
[0144] The chemical composition and weight percentage of the high temperature titanium alloy ingot 6 are: Al: 6.0%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 2.5%, Si: 0.50%, W: 1.2%, C: 0.055%, Ti: balance.
[0145] The steps of processing and heat treating the high temperature titanium alloy ingot 6 include:
[0146] (1) The high temperature titanium alloy ingot 6 is subjected to first stage upsetting deformation at temperatures of 1180° C., 1120° C. and 1030° C. in sequence, with a deformation amount of 45%;
[0147] After measurement, the T of the titanium alloy after the first stage of upsetting β The temperature is 1040℃, and the primary heat treatment is: keep the temperature at 950℃ for 180min, then heat up to 1065℃ and keep the temperature for 120min, then take out of the furnace and air cool;
[0148] The second stage of upsetting: 8 times of upsetting deformation at 1030℃, with a deformation of 45%;
[0149] (2) The forging obtained in step (1) is subjected to solution aging heat treatment: at a temperature of 1020° C., kept for 2 h, and air-cooled; at a temperature of 700° C., kept for 5 h, and air-cooled, to obtain a high-temperature titanium alloy forging 6.
[0150] The mechanical properties of high temperature titanium alloy forging 6 are shown in Table 6:
[0151] Table 6
[0152]
[0153] Comparative Example 2
[0154] The chemical composition and weight percentage of the high temperature titanium alloy ingot 7 are: Al: 5.9%, Sn: 4.0%, Zr: 3.5%, Mo: 0.30%, Nb: 0.40%, Ta: 2%, Si: 0.40%, W: 0.8%, C: 0.055%, Ti: balance.
[0155] The steps of processing and heat treating the high temperature titanium alloy ingot 7 include:
[0156] (1) The high temperature titanium alloy ingot 7 is subjected to first stage upsetting deformation at temperatures of 1180° C., 1120° C. and 1030° C. in sequence, with a deformation amount of 45%;
[0157] After measurement, the T of the titanium alloy after the first stage of upsetting β The temperature is 1040℃, and the primary heat treatment is: keep the temperature at 950℃ for 180min, then heat up to 1065℃ and keep the temperature for 120min, then take out of the furnace and air cool;
[0158] The second stage of upsetting: 8 times of upsetting deformation at 1030℃, with a deformation of 45%;
[0159] (2) The forging obtained in step (1) is subjected to solution aging heat treatment: at a temperature of 1020° C., kept for 2 h, and air-cooled; at a temperature of 700° C., kept for 5 h, and air-cooled, to obtain a high-temperature titanium alloy forging 7.
[0160] The mechanical properties of high temperature titanium alloy forging 7 are shown in Table 7:
[0161] Table 7
[0162]
[0163] Comparative Example 3
[0164] The chemical composition and weight percentage of the high temperature titanium alloy ingot 8 are: Al: 6.0%, Sn: 4.0%, Hf: 3.5%, Mo: 0.30%, Nb: 0.40%, Ta: 2.5%, Si: 0.40%, W: 0.8%, C: 0.055%, Ti: balance.
[0165] The steps of processing and heat treating the high temperature titanium alloy ingot 8 include:
[0166] (1) The high temperature titanium alloy ingot 8 is subjected to first stage upsetting deformation at temperatures of 1180° C., 1120° C. and 1030° C. in sequence, with a deformation amount of 45%;
[0167] After measurement, the T of the titanium alloy after the first stage of upsetting βThe temperature is 1040℃, and the primary heat treatment is: keep the temperature at 950℃ for 180min, then heat up to 1065℃ and keep the temperature for 120min, then take out of the furnace and air cool;
[0168] The second stage of upsetting: 8 times of upsetting deformation at 1030℃, with a deformation of 45%;
[0169] (2) The forging obtained in step (1) is subjected to solution aging heat treatment: at a temperature of 1020°C, keeping warm for 2 hours, and air cooling; at a temperature of 700°C, keeping warm for 5 hours, and air cooling, to obtain a high-temperature titanium alloy forging 8.
[0170] The mechanical properties of high temperature titanium alloy forging 8 are shown in Table 8:
[0171] Table 8
[0172]
[0173] Comparative Example 4
[0174] When Ta≤2.0%, Si is less than 0.6%, and other components and their contents are within the specified range, the microstructure and properties of the alloy prove the coordinated effect of the two on the creep properties of the alloy.
[0175] The chemical composition and weight percentage of the high temperature titanium alloy ingot 9 are: Al: 6.0%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 1%, Si: 0.50%, W: 0.8%, C: 0.055%, Ti: balance.
[0176] The steps of processing and heat treating the high temperature titanium alloy ingot 9 include:
[0177] (1) The high temperature titanium alloy ingot 9 is subjected to first stage upsetting deformation at temperatures of 1180° C., 1120° C. and 1030° C. in sequence, with a deformation amount of 45%;
[0178] After measurement, the T of the titanium alloy after the first stage of upsetting β The temperature is 1040℃, and the primary heat treatment is: keep the temperature at 950℃ for 180min, then heat up to 1065℃ and keep the temperature for 120min, then take out of the furnace and air cool;
[0179] The second stage of upsetting: 8 times of upsetting deformation at 1030℃, with a deformation of 45%;
[0180] (2) The forging obtained in step (1) is subjected to solution aging heat treatment: at a temperature of 1020° C., kept for 2 h, and air-cooled; at a temperature of 700° C., kept for 5 h, and air-cooled, to obtain a high-temperature titanium alloy forging 9.
[0181] The mechanical properties of high temperature titanium alloy forging 9 are shown in Table 9:
[0182] Table 9
[0183]
[0184] Performance Testing
[0185] The high-temperature titanium alloys in the examples and comparative examples were formed at the respective second-stage upsetting temperatures to prepare integral blisk forgings; wherein the integral blisk forgings had an outline dimension of 210 mm in diameter × 50 mm, and the integral blisk parts were obtained after machining.
[0186] The super-rotation rupture test method was used to test the super-rotation rupture performance of the integral blade disk assembly under high temperature, high pressure and high speed environment. The super-rotation rupture performance test curve of the integral blade disk parts made of high-temperature titanium alloy 1 is shown in the figure. Figure 6-8 As shown in the test results, the integral blade disk parts made of high-temperature titanium alloy 1 did not show significant changes in size and cracks when the temperature was 650°C and the rotation speed was 115% and 122% respectively, and the rotation time was 520s and 530s; when the temperature was 650°C and the rotation speed was 150%, and the rotation time was 675s, the integral blade disk parts did not show significant changes in size and the test piece broke.
[0187] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A high temperature titanium alloy, characterized in that: The chemical composition and weight percentage of the high-temperature titanium alloy are Al: 6.0%-8.0%, Sn: 2.5%-4.5%, Zr: 2.5%-7.0%, Hf: 0.5%-1.5%, Mo: 0.05%-0.85%, Nb: 0.20%-0.80%, Ta: 1.0%-3.0%, Si: 0.40%-0.90%, W: 0.4%-1.0%, C: 0.05%-0.07%, and Ti balance.
2. The high temperature titanium alloy according to claim 1, characterized in that: In the chemical composition and weight percentage of the high temperature titanium alloy, when Ta≤2.0%, Si≥0.6%.
3. The high temperature titanium alloy according to claim 1, characterized in that: The chemical composition and weight percentage of the high-temperature titanium alloy are Al: 6.0%-8.0%, Sn: 2.5%-4.5%, Zr: 2.5%-3.5%, Hf: 0.5%-1.0%, Mo: 0.05%-0.85%, Nb: 0.20%-0.80%, Ta: 1.0%-3.0%, Si: 0.5%-0.9%, W: 0.4%-1.0%, C: 0.05%-0.07%, and Ti as a balance.
4. The high temperature titanium alloy according to claim 1, characterized in that: The chemical composition and weight percentage of the high-temperature titanium alloy are: Al: 6.0%, Sn: 3.8%, Zr: 2.5%, Hf: 1%, Mo: 0.30%, Nb: 0.40%, Ta: 2.3%, Si: 0.60%, W: 0.80%, C: 0.05%-0.07%, Ti: balance.
5. The high temperature titanium alloy according to claim 1, characterized in that: The chemical composition and weight percentage of the high-temperature titanium alloy are: Al: 6.0%, Sn: 4.0%, Zr: 3.5%, Hf: 0.5%, Mo: 0.30%, Nb: 0.40%, Ta: 1.0%, Si: 0.90%, W: 0.80%, C: 0.05%-0.07%, Ti: balance.
6. The high temperature titanium alloy according to any one of claims 1 to 5, characterized in that: The R of the high temperature titanium alloy at 25°C m ≥1000MPa, R p0.2 ≥900MPa, A5≥6%; R at 650℃ m ≥610MPa, R p0.2 ≥500MPa; creep residual strain under the test conditions of temperature 650℃, creep stress 120MPa and time 100h ≤0.18%; R at 700℃ m ≥560MPa, R p0.2 ≥450MPa; creep residual strain ≤0.18% under the test conditions of temperature 700℃, creep stress 70MPa and test time 100h.
7. A method for preparing the high temperature titanium alloy according to any one of claims 1 to 6, characterized in that: The method comprises: (1) weighing the metal and / or the master alloy according to the chemical composition and weight percentage of the high-temperature titanium alloy, smelting, and obtaining a titanium alloy ingot; (2) forging and deforming the titanium alloy ingot to obtain a forging blank; (3) The forging blank is subjected to solution heat treatment and aging heat treatment in sequence to obtain the high-temperature titanium alloy.
8. The method according to claim 7, characterized in that In step (2), the forging deformation specifically includes a first stage upsetting, a primary heat treatment and a second stage upsetting, wherein the first stage upsetting includes three upsettings, specifically: the titanium alloy ingot is subjected to one upsetting deformation at temperatures of 1150°C to 1400°C, 1100°C to 1300°C and 1000°C to 1100°C, respectively, and the deformation amount is controlled at 40%-50%.
9. The method according to claim 7, characterized in that: In step (3), the temperature of the solution heat treatment is T β -25℃~T β -10℃, time is 1-3h; And / or, the aging heat treatment is performed at a temperature of 700°C-800°C and for a time of 4-7h.
10. Application of the high temperature titanium alloy according to any one of claims 1 to 6 in aircraft engine parts, characterized in that: The aero-engine parts are blisks, blades and turbine disks.
Citation Information
Patent Citations
Novel heat-resisting titanium alloy and processing and manufacturing method and application thereof
CN104018027A
High-temperature and high-strength titanium alloy and preparation method thereof
CN104611610A
Iron aluminide useful as electrical resistance heating element
CN1140203A
Preparation method of high-strength 650 DEG C high-temperature titanium alloy large-size blisk forging
CN115007775A
Heat-resistant high-temperature titanium alloy and hot working method thereof
CN115261671A
